Test-Retest Reliability of the Political Elites Aversive Personality Scale (PEAPS) - Maier, Jürgen; Oschatz, Corinna; Dian, Mona; Zettler, Ingo (Studia Psychologica: Theoria et praxis, 2024)
Although aversive (“dark”) personality characteristics of politicians have increasingly become a focus of research, a suitable self-assessment inventory for political elites has only recently been introduced. This article examines the test-retest reliability of the Political Elites Aversive Personality Scale (PEAPS) in a unique natural setting using a panel study of candidates running for the 2021 Berlin state election and the 2023 Berlin repeated election (N = 106, 37.7% female). The average age was 47.5 (2021) and 49.5 years (2023), respectively (SD = 14.7 years). 14.2% of the participants ran for the Green Party (Bündnis 90/Die Grünen), 11.3% for the Liberal Party (FDP), 8.5% for the Social Democrats (SPD), 7.5% for the Alternative for Germany (AfD), 6.6% for the Christian Democrats (CDU), 4.7% for the Left Party (Die Linke), and 48.1% for smaller parties not represented in the parliament. Across various methods, we find moderate to high levels of reliability. Especially in the light of the relatively long time lag between the measurement occasions, results thus support using PEAPS for self-assessment of aversive personality of politicians. Given that PEAPS comprises six items only, it appears to be suitable for measuring aversive personality in situations in which time or cost prevent the use of more comprehensive personality measures. We also suggest that future research might aim to test the usefulness of PEAPS for other elites (e.g., corporate leaders).